MO022EVALUATION OF THE EFFECT OF TOLVAPTAN ON OXIDATIVE STRESS IN PATIENTS WITH AUTOSOMAL DOMINANT POLYCYSTIC KIDNEY DISEASE (ADPKD). (29th May 2021) - Rigato, Matteo; Bertoldi, Giovanni; Ravarotto, Verdiana; Carraro, Gianni; Calò, Lorenzo
Abstract: Background and Aims: Autosomal dominant polycystic kidney disease (ADPKD) is the most frequent monogenic kidney disease, with approximately 12.5 million affected people worldwide, and it is responsible for over 10% of patients with end-stage renal disease (ESRD) with an important impact on public health. It causes progressive renal failure and other extrarenal manifestations, including endothelial dysfunction and hypertension. These complications are both linked to reduced nitric oxide levels related to excessive Oxidative Stress (OxSt) that different studies confirm occurring in the early stages of ADPKD. This study aims to evaluate ex vivo through a molecular biology approach the OxSt status of ADPKD patients under treatment with tolvaptan (Jinarc) and compare with both a group of untreated young ADPKD subjects with preserved renal function (eGFR> 80 mL/min/1.73m2) and a cohort of healthy subjects as controls. Methods: In mononuclear cells of 9 ADPKD patients treated with tolvaptan, 9 untreated ADPKD patients with preserved renal function (eGFR> 80 mL/min/1.73m2) and 9 healthy subjects we evaluated the state of OxSt in terms of protein expression of p22phox, subunit of NADH/NADPH oxidase essential for the production of superoxide; protein expression of Heme oxygenase (HO)-1, protective from OxSt and anti-inflammatory and MYPT-1 phosphorylation, marker of Rho kinase activation, deeply involved in OxSt signaling for the induction of cardiovascular-renal remodeling; Results: In patients with tolvaptan treated ADPKD, protein expression of p22phox and phosphorylation state of MYPT-1 were significantly reduced compared to untreated young ADPKD subjects with normal GFR (p=0.01 and p=0.03, respectively). Phosphorylation of MYPT-1 was significantly reduced in patients treated with tolvaptam vs untreated patients and also when compared to healthy controls (p=0.01 for both). HO-1 levels of treated ADPKD patients were significantly higher both vs untreated ADPKD patients with normal GFR (p=0.04) and vs healthy controls (p=0.01) Conclusions: Tolvaptan is reported to reduce the rate of GFR deterioration of 1.20 mg/mL/year compared to placebo. Several animal studies have demonstrated the ability of tolvaptan to reduce OxSt and increase HO-1. Our study showed "ex vivo" in humans that in ADPKD patients tolvaptan reduces the OxSt state compared to untreated ADPKD with normal GFR and increases the antioxidant HO-1, in addition to reduce Rho kinase activation, further supporting its renoprotective effect also in terms of OxSt inhibition. This study confirms for the first time in humans that tolvaptan is effective on the reduction of intracellular OxSt and may impair the biochemical/molecular mechanisms that contribute to the worsening of renal function, endothelial damage and hypertension.